Food insecurity among public university students receiving financial assistance in Malaysia - Sulaiman, Norhasmah; Md Jusoh, Zuroni; Abd Razak, Siti Marhana (Persatuan Ekonomi Pengguna dan Keluarga Malaysia (MACFEA), 2012)
The objectives of the study were to determine the prevalance and the consequences of food insecurity among public university (IPTA) students receiving financial assistance in Peninsular Malaysia. Four Public Universiti in peninsular Malaysia were randomly selected namely University Malaysia Perlis (UNIMAP) (131 respondents), Universiti Malaya (UM) (120 respondents), Universiti Teknikal Malaysia Melaka (UTeM) (115 respondents) and University Sultan Zainal Abidin (UNiSZA) (118 respondents). A total of 484 respondents were selected through multi-stage random sampling. Respondents were interviewed using a structured questionnaire to obtain information on their demographic and socio-economic characteristics, food security status, dietary intake and health-related quality of life. Results indicates that 73.7% of the respondents reported that the amount of financial assistance receiving from the agencies was not sufficient. Approximately 67.1% of the respondents had some kind of food insecurity .Two types of coping strategies apply by respondents to prevent food insecurity i.e. food related coping strategies and non-food coping strategies. About 17.4% and 8.1% of respondents were overweight and obesity, respectively. Lack of micronutrients intake (i.e. vitamin and mineral) is the major findings identified in this study. Domains related to the mental health status show relatively lower compared to physical health status among the respondents. In conclusion, university and related agencies should provide meal plan for their students who have problem to buy food due to financial problems.